Pengaruh Akupresur pada Titik SP 8 dan SP 10 terhadap Intensitas Nyeri Remaja yang Mengalami Dismenore - Ni Luh Putu Linda Gayatri; Dewa Made Ruspawan; Ni Nyoman Hartati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
Dysmenorrhea is a gynecological complaint due to an imbalance of the hormone progesterone in the blood, causing pain. Adolescent girls who experience menarche have some disturbances of cramps, pain and discomfort associated with menstruation which is called dysmenorrhea and most adolescents experience varying levels of cramps, pain due to an imbalance of the hormone progesterone in the blood resulting in pain. One of the factors that cause dysmenorrhea is stress which can interfere with the work of the endocrine system, so that it can cause irregular menstruation and cause pain during menstruation. This study aims to determine the effect of acupressure at points SP 8 and SP 10 on the pain intensity of -adolescents who experience dysmenorrhea at the Department of Nursing, Poltekkes, Ministry of Health, Denpasar in 2022. This type of research was pre-experimental with a pre-post-test design in one group (one group pre-test). -post test design) using purposive sampling technique. The total population in the study was 43 people. The number of samples is 39 people. Data was collected using the NRS measurement sheet. The results showed that there was a significant decrease in the dysmenorrhea pain scale after being given acupressure at the SP 8 and SP 10 points with p-value = 0.000 (0.05), this means that Ha is accepted so that there is an influence of SP 8 and SP 10 acupressure points on the pain intensity of adolescents with dysmenorrhea.